Foreign Direct Investment Regulation in the European Union : A Balancing Act Between Free Movement of Capital and National Security Interests - Leinonen, Stella (My University, 2023)
EU’s liberal FDI regime has attracted foreign investors for decades. The number of acquisitions by Chinese companies especially in strategically sensitive industries grew significantly in the beginning of the 21st century, which raised security concerns in the Member States as well as the Union as a whole. As a result, the EU adopted a Framework Regulation (EU) 2019/452 establishing a legal framework for the coordination of the screening of inward FDIs into the territory of the EU, which became fully operational as of 11 October 2020. The Regulation was established to complement the national screening mechanisms Member States may choose to implement on the basis of general security clause Article 4(2) TEU and Article 65(1)(b) TFEU allowing Member States to take measures restricting the free movement of capital justified on the grounds of public policy or public security. While the Regulation aims to set up certain guidelines for the national screening of FDIs, the Member States hold the power to determine the grounds of their national public policy and public security. This thesis systemizes the legal framework around fundamental principles of the EU and the concepts of public security and public policy in relation to Member States’ national FDI screening mechanisms and the Regulation. The goal of this these is to examine, 1) how are the fundamental principles of free movement of capital and freedom of establishment assessed in the application of the Regulation, and 2) how the notions of public security and public policy are to be defined in the application of the Regulation. The study is conducted based on the legal dogmatic approach, and focuses to analyze and interpret the current EU legislation around the topic. While the ECJ has established in its case law that a wider range of restrictions can be justified in respect of capital movements between Member States and third countries than what is accepted on capital movements inside the EU, this thesis argues that a stricter threshold for the application of public security and public policy exceptions in FDI screening should be established. Furthermore, it is concluded, that the Member States’ power to determine the grounds of their national security and public policy is limited by international commitments, general principles of EU law and case law on the application of Article 65(1) TFEU, nevertheless allowing each Member State significant latitude for self-determination. This paper argues that high emphasis on EU’s part on a stricter application of the grounds of public security and public order is required through case law and guidelines.

EU on avoimella sijoituspolitiikallaan houkutellut ulkomaisia suoria sijoituksia vuosikymmenien ajan. Kiinalaisten investointien määrä erityisesti strategisesti merkittävillä toimialoilla kasvoi merkittävästi 2000-luvun alussa, mikä herätti turvallisuushuolia sekä jäsenvaltioissa että unionitasolla. Näistä lähtökohdista astui voimaan Euroopan parlamentin ja neuvoston asetus ulkomaisten suorien sijoitusten seurannasta (EU) 2019/452, joka loi puitteet EU:n alueelle suuntautuvien suorien ulkomaisten sijoitusten kansallisen seulonnan koordinoinnille ja seurannalle. Asetusta ryhdyttiin kokonaisvaltaisesti soveltamaan 11. lokakuuta 2020. Asetus täydentää kansallisia seulontamekanismeja, joita jäsenvaltiot voivat päättää perustaa SEU-sopimuksen 4 artiklan 2 kohdan ja SEUT-sopimuksen 65 artiklan 1 kohdan b alakohdan perusteella. Jäsenvaltiot voivat toteuttaa toimenpiteitä, jotka rajoittavat pääoman vapaata liikkuvuutta yleiseen järjestykseen tai yleiseen turvallisuuteen perustuvista syistä. Asetuksella pyritään laatimaan tiettyjä suuntaviivoja suorien ulkomaisten sijoitusten kansallista seulontaa varten, mutta jäsenvaltioilla säilyy oikeus määritellä oman kansallisen yleisen järjestyksensä ja yleisen turvallisuutensa perusteet. Tämän tutkielman analyysi rakentuu EU:n perusperiaatteiden sekä yleisen turvallisuuden ja yleisen järjestyksen käsitteiden tarkastelulle suhteessa asetukseen ja jäsenvaltioiden kansallisiin ulkomaisten suorien sijoitusten seulontamekanismeihin. Tutkielman tarkoituksena on selvittää, 1) miten pääoman vapaan liikkuvuuden ja sijoittautumisvapauden perusperiaatteet arvioidaan asetusta sovellettaessa, sekä 2) miten yleisen turvallisuuden ja yleisen järjestyksen käsitteet määritellään asetusta sovellettaessa. Tutkimus perustuu oikeusdogmaattiseen lähestymistapaan ja keskittyy analysoimaan ja tulkitsemaan EU:n nykyistä lainsäädäntöä ja oikeuskäytäntöä aiheen ympärillä. Vaikka Euroopan unionin tuomioistuin on todennut oikeuskäytännössään, että jäsenvaltioiden ja kolmansien maiden väliseen pääoman liikkuvuuteen voidaan soveltaa laajempaa joukkoa rajoituksia kuin EU:n sisäisissä pääomanliikkeissä hyväksytään, tässä tutkielmassa esitetään, että yleisen turvallisuuden ja yleisen järjestyksen poikkeuksien soveltamisessa tulee noudattaa nykyistä korkeampaa kynnystä. Lisäksi todetaan, että kansainväliset sitoumukset, EU:n oikeuden yleiset periaatteet ja SEUT-sopimuksen 65 artiklan 1 kohdan soveltamista koskeva oikeuskäytäntö rajoittavat jäsenvaltioiden toimivaltaa määrittää kansallisen turvallisuutensa ja yleisen järjestyksensä perusteet. Tästä huolimatta jokaisella jäsenvaltiolla on huomattava itsemääräämisvapaus käsitteiden määrittelyssä. Tässä tutkielmassa esitetään, että EU:n on oikeuskäytännön ja suositusten kautta painotettava rajoitetumpaa yleiseen turvallisuuteen ja yleiseen järjestykseen perustuvien syiden soveltamista.
Keywords: EU Law, investment law, free movement of capital, freedom of establishment, foreign direct investments, public security, EU-oikeus, sijoituslainsäädäntö, pääoman vapaa liikkuvuus, sijoittautumisoikeus, ulkomaiset suorat investoinnit, yleinen turvallisuus